Chloroplast Genome Traits Correlate With Organismal Complexity and Ecological Traits in Chlorophyta - Fang, Jiao; Chen, Yangliang; Liu, Guoxiang; Verbruggen, Heroen; Zhu, Huan (Frontiers in Ecology and Evolution, 2021)
A positive relationship between cell size and chloroplast genome size within chloroplast-bearing protists has been hypothesised in the past and shown in some case studies, but other factors influencing chloroplast genome size during the evolution of chlorophyte algae have been less studied. We study chloroplast genome size and GC content as a function of habitats and cell size of chlorophyte algae. The chloroplast genome size of green algae in freshwater, marine and terrestrial habitats was differed significantly, with terrestrial algae having larger chloroplast genome sizes in general. The most important contributor to these enlarged genomes in terrestrial species is the length of intergenic regions. There was no clear difference in the GC content of chloroplast genomes from the three habitats categories. Functional morphological categories also showed differences in chloroplast genome size, with filamentous algae having substantially larger genomes than other forms of algae, and foliose algae had lower GC content than other groups. Chloroplast genome size showed no significant differences among the classes Ulvophyceae, Trebouxiophyceae and Chlorophyceae, but the GC content of Chlorophyceae chloroplast genomes is significantly lower than that of Ulvophyceae and Trebouxiophyceae. There is a certain positive relationship between chloroplast genome size and cell size for the Chlorophyta as a whole and within each of three major classes. our data also confirms previous reports that ancestral quadripartite architecture has been lost many times independently in Chlorophyta.